A Case of Small Cell Carcinoma With Adenocarcinoma Found in a Rectal Fissure. Issue 1 (January 2019) - Harinath, Lakshmi; Mohanty, Alok; Pai, Reetesh K.; Islam, Mohammed; Silverman, Jan F.
Abstract : Abstract: Small cell carcinomas are aggressive high-grade malignancies most commonly diagnosed in the lung, but can also be found in extrapulmonary sites such as the breast, kidney, urinary bladder, uterus, ovary, pancreas, hepatobiliary tree, thymus, skin, and salivary glands. Although the gastrointestinal system has an abundance of neuroendocrine cells, small cell carcinomas in this region have a low incidence. We present the case of a 51-year-old man with a history of pain with bowel movements and recent weight loss. Colonoscopy was performed, which revealed a rectal fissure with a lesion involving the rectum and anal canal. Biopsy of the lesion revealed invasive carcinoma with 2 distinct morphologies, a poorly differentiated small cell component and a minor adenocarcinoma component. We discuss the differential diagnosis of small cell carcinoma that includes mixed adenoneuroendocrine carcinomas and other neuroendocrine neoplasms.